Low-cost indoor navigation and environment mapping of an unmanned aerial vehicle (UAV) - Xu, Yuecong (2017)
Unmanned Aerial Vehicles, or UAV, have gain its popularity in both military, personal and commercial use. Small and medium sized UAVs are capable of multiple missions such as detection and searching both indoors and outdoors. In recent years, navigating through indoor unknown environment has gradually become a key feature of autonomous Unmanned Aerial Vehicles (UAVs) especially during military as well as disaster reconnaissance operations. Currently, most autonomous UAVs use laser scanners which are quite accurate, but they are very costly. It increases the cost of a UAV system which lifted the criteria of using autonomous UAVs. This project documents the design and development of a low-cost environment mapping and autonomous control of UAVs using cameras as the basic detection tool. The end result is an intelligent UAV, capable of autonomous indoor navigation via data from the camera, and capable of mapping out the indoor environment.